STATISTICS FOR MANAGEMENT - LEVIN I RICHARD; RUBIN S DAVID (NOIDA PEARSON EDUCATION INC DORLING KINDERSLEY INDIA PVT LTD, 2011)
"Statistics for Management" by Richard I. Levin and David S. Rubin is a comprehensive textbook designed to make statistical concepts and their applications in the business world accessible to students and professionals. The book is lauded for its practical and real-world approach, prioritizing intuitive understanding over complex mathematical notations. It aims to equip managers with the statistical tools necessary for informed decision-making.
STATISTICS
STATISTICS
BBA & MBA
Keywords: STATISTICS; MANAGEMENT